Design of an Advanced Membrane Electrode Assembly Employing a Double-Layered Cathode for a PEM Fuel Cell - Kim, GyeongHee; Eom, KwangSup; Kim, MinJoong; Yoo, Sung Jong; Jang, Jong Hyun; Kim, Hyoung-Juhn; Cho, EunAe (American Chemical Society, 2015)
The membrane electrolyte assembly (MBA) designed in this study utilizes a double-layered cathode: an inner catalyst layer prepared by a conventional decal transfer method and an outer catalyst layer directly coated on a gas diffusion layer. The double-layered structure was used to improve the interfacial contact between the catalyst layer and membrane, to increase catalyst utilization and to modify the removal of product water from the cathode. Based on a series of MEAs with double-layered cathodes with an overall Pt loading fixed at 0.4 mg cm(-2) and different ratios of inner-to-outer Pt loading the MBA with an inner layer of 0.3 mg Pt cm(-2) and an outer layer of 0.1 mg Pt cm(-2) exhibited the best performance. This performance was better than that of the conventional single-layered electrode by 13.5% at a current density of 1.4 A cm(-2).
Keywords: GAS-DIFFUSION LAYER; WATER MANAGEMENT; PERFORMANCE; FABRICATION; DEGRADATION; DURABILITY; PRESSURE; GDLS